Macroeconomic Adjustment in Bolivia since the 1970s: Adjustment to What, By Whom, and How? Analytical Insights from a SAM Model - Luis Carlos Jemio M. (Kiel Institute of World Economics (IfW), 2001)
This paper discusses alternative adjustment patterns in Bolivia over the last three decades using a SAM-based model that explicitly separates formal from informal activities, includes separate accumulation balance adjustments for different economic agents, differentiates closures by periods of time, and incorporates balances for all sectors of the economy. It is argued that both, fluctuating capital inflows and terms of trade as well as the stabilization policies and the structural reforms, affected different groups differently. Moreover, the various adjustment patterns followed by the groups have determined the direction of adjustment at the macroeconomic level. Thus, macroeconomic adjustment in Bolivia has been the outcome of sectoral adjustments and of the interactions among different agents through the diverse markets they operate in.
Keywords: E6; O54; C68; E65; 330; Macroeconomic adjustment; Social Accounting Matrix; Bolivia; Wirtschaftliche Anpassung; Wirtschaftspolitische Wirkungsanalyse; Social Accounting Matrix; Mehr-Sektoren-Modell; Bolivien